Depression and anxiety screening in emergency department patients with recurrent abdominal pain: An evidence synthesis for a clinical practice guideline. (19th October 2021) - Oliveira J. e Silva, Lucas; Prakken, Steven D.; Meltzer, Andrew C.; Broder, Joshua S.; Gerberi, Danielle J.; Upadhye, Suneel; Carpenter, Christopher R.; Bellolio, Fernanda
Abstract: Background: Recurrent abdominal pain in the emergency department (ED) might represent an opportunity for screening of depression and/or anxiety. Methods: We systematically searched five databases for studies evaluating the effect of screening for depression and/or anxiety in ED patients with recurrent and undifferentiated abdominal pain. Given paucity of direct evidence, we also searched for indirect evidence including studies that assessed prevalence of depression and/or anxiety in EDs (not necessarily recurrent abdominal pain), diagnostic accuracy of screening tools, effectiveness of screening in other settings, and outcomes such as repeat ED visits of patients with abdominal pain who were screened in the ED. Two methodologists evaluated certainty in the evidence using the GRADE approach. Results: A total of 4, 337 citations were reviewed, and zero studies were found on the effect of screening in patients with recurrent and undifferentiated abdominal pain in the ED. A total of 35 studies were included as relevant indirect evidence. In studies of ED patients with abdominal pain, depression ranged from 10% to 29%, while anxiety ranged from 18% to 50%. False positives appear to be an issue given relatively low specificity of screening tools. One randomized trial including ED patients with vague symptoms evaluated the effect of depression screening on a composite outcome of depression recognition, psychiatric consultation, or referral by the emergency physician (risk ratio = 1.49, 95% confidence interval [CI] = 0.49 to 4.53, very low certainty). One study reported that patients with undifferentiated abdominal pain who screened positive for depression have had increased ED recidivism (odds ratio = 3.17, 95% CI = 1.14 to 8.85, very low certainty). Conclusions: We were unable to identify any evidence that confirms that depression or anxiety screening in ED patients with recurrent and undifferentiated abdominal pain improves outcomes or changes management downstream.